Adieu, Paris ! de Simone Routier à la croisée de l’intime et du médiatique - Mylène Bédard (Contextes)
This article proposes to highlight the relationship of the French Canadian writer Simone Routier to the press, which appears to be based on a fine understanding of the economic, political stakes, the mobility in the literary field and of prestige that are associated to it. In order to prove this, I will linger over her diary of evacuation Adieu, Paris !, that joins between the diary and the report of war, as well as her daily collaboration on L’Événement during her European stay (1930-1940). The form of the report that modulates Routier’s diary is also compatible with the strategy of success preferred by the writer since she stages a figure, the reporter one, who wants to unifier.  The analysis of the impact of the media in Routier’s narrative makes of its evacuation, which touches both the poetics, the ethos’s form built by the writer, will better grasp the particular status of the text, at the same time order, personal diary and war report, its political aims and its decisive role in the trajectory of the woman of letters.